Reappraising An Innovation in Rural Nursing Education 1984-Present - Alison Schell Witte (Rural Nurse Organization; Binghamton University, 2015)
Presented at the 2014 International Rural Health & Rural Nursing Research Conference Co-Sponsored by the Montana State University College of Nursing and the Rural Nurse Organization (RN0). DOI:  http://dx.doi.org/10.14574/ojrnhc.v15i1.376